2001
DOI: 10.1111/1468-0297.00659
|View full text |Cite
|
Sign up to set email alerts
|

Do Benefit Cuts Boost Job Finding? Swedish Evidence from the 1990s*

Abstract: In June 1995, the Swedish parliament decided to cut the replacement rate in unemployment insurance from 80% to 75%, a change that took effect on 1 January 1996. The paper exploits a quasi-experimental feature of the bene®t reform to examine the effect on job ®nding. We compare the evolution of transitions to employment before and after the reform among those affected and those not affected. Our estimates suggest that the reform caused an increase in the transition rate of roughly 10%. Moreover, the reform appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
102
3
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 34 publications
11
102
3
1
Order By: Relevance
“…their Figure 3). Carling, Holmlund and Vejsiu (2001) find a significant and large negative UI effect on job finding rates. Ackum Agell, Björklund and Harkman (1995) find that prolonged spells of benefit-program periods are quite common in Sweden, while Hägglund (2000) detects a very interesting sensitivity of employment duration as well as time spent on a program to changes in the UI work requirement.…”
Section: Treatment Effects By Month Of Placement and Work-disincentivmentioning
confidence: 79%
See 1 more Smart Citation
“…their Figure 3). Carling, Holmlund and Vejsiu (2001) find a significant and large negative UI effect on job finding rates. Ackum Agell, Björklund and Harkman (1995) find that prolonged spells of benefit-program periods are quite common in Sweden, while Hägglund (2000) detects a very interesting sensitivity of employment duration as well as time spent on a program to changes in the UI work requirement.…”
Section: Treatment Effects By Month Of Placement and Work-disincentivmentioning
confidence: 79%
“…We can thus be reasonably confident that most of our individuals are indeed first-time unemployed. 10 Following Carling, Holmlund and Vejsiu (2001) unemployment durations have been slightly adjusted in order to disregard short interruptions of the spells. Two adjacent unemployment spells separated by a short (≤7 days) break 6 4.…”
mentioning
confidence: 99%
“…The evidence on this point is mixed. While US and UK studies typically provide benefit elasticity estimates (the elasticity of unemployment duration with respect to the level of the unemployment benefit) ranging from 0.2 to 0.9 (Moffitt, 1985;Narendranathan et al, 1985;Katz and Meyer, 1990;Meyer, 1990;Card and Levine, 1998), European elasticity estimates differ widely, from virtually zero (Hujer and Schneider, 1989;Groot, 1990;van den Berg, 1990;Steiner, 1990;Hernaes and Strøm, 1996) to above unity (Abbring et al, 1998;Carling et al (1999).…”
Section: Introductionmentioning
confidence: 99%
“…Coefficient estimates and significance levels vary slightly with the length of the response period, but the main results reported in this subsection remain virtually unchanged. 21 Using data from the mid-1990s, Carling et al (1999) found a similar pattern in a study of how job-finding rates were affected by a reduction in replacement rates. In other studies using data from the early 1990s, e.g.…”
Section: The Employment Equationmentioning
confidence: 79%